2021
DOI: 10.1097/pai.0000000000000936
|View full text |Cite
|
Sign up to set email alerts
|

ALK-Negative Anaplastic Large Cell Lymphoma (ALCL): Prognostic Implications of Molecular Subtyping and JAK-STAT Pathway

Abstract: The anaplastic lymphoma kinase (ALK)-negative anaplastic large cell lymphoma (ALCL) is a clinically distinct but heterogeneous entity and lacks the specific immunophenotypic or genetic features compared with the ALK-positive ALCL. Recent molecular studies have provided genetic landscapes of ALK-negative ALCL that have prognostic significance. In this study, we subtyped ALK-negative ALCL based on DUSP22 rearrangements and TP63 expression and also looked for mutations in JAK-STAT pathway. The subtyping of the AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
4
11
0
Order By: Relevance
“…We found that p-STAT3 was expressed in 22 of 45 (48.8%) ALK − ALCL cases, whereas JAK1/3 and/or STAT3 mutations were only detected in 4 of 21 (19%) ALK − ALCL cases. These results support previous observations that various mechanisms can lead to the activation of the JAK/STAT3 signaling pathway in ALK − ALCL cases, and it is not restricted to JAK and/or STAT3 mutations 6,12. Interestingly, we observed that 1 p-STAT3 + case harbored loss-of-function mutations in the gene encoding SOCS1 protein.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that p-STAT3 was expressed in 22 of 45 (48.8%) ALK − ALCL cases, whereas JAK1/3 and/or STAT3 mutations were only detected in 4 of 21 (19%) ALK − ALCL cases. These results support previous observations that various mechanisms can lead to the activation of the JAK/STAT3 signaling pathway in ALK − ALCL cases, and it is not restricted to JAK and/or STAT3 mutations 6,12. Interestingly, we observed that 1 p-STAT3 + case harbored loss-of-function mutations in the gene encoding SOCS1 protein.…”
Section: Discussionsupporting
confidence: 92%
“…These results support previous observations that various mechanisms can lead to the activation of the JAK/ STAT3 signaling pathway in ALK − ALCL cases, and it is not restricted to JAK and/or STAT3 mutations. 6,12 Interestingly, we observed that 1 p-STAT3 + case harbored loss-of-function mutations in the gene encoding SOCS1 protein. This protein negatively regulates STAT3 signal transduction in ALK − ALCLs and a mutation in the gene may contribute to constitutive STAT3 phosphorylation.…”
Section: Discussionmentioning
confidence: 80%
“…DUSP22 rearrangement has been reported most often in cases of systemic ALK-negative ALCL and primary cutaneous ALCL, occasionally in lymphomatoid papulosis and rarely in peripheral T cell lymphoma, NOS, but not in ALK+ ALCL [23,24]. DUSP22 rearrangement occurs in 13-30% of ALK-negative ALCL cases [6,[8][9][10][11]. Consistent with prior reports, 27% of systemic ALK-negative ALCL cases in the present study harbored DUSP22 rearrangement.…”
Section: Discussionsupporting
confidence: 89%
“…ALK-negative ALCL is a genetically heterogeneous entity, with 13-30% of cases harboring DUSP22 rearrangement (R) and 2-8% of cases carrying TP63-R [6,[8][9][10][11]. TP63 and DUSP22 rearrangements are nearly mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%
“…TP63 contributes to maintaining redox homeostasis through glutathione biogenesis, utilization, and regeneration. TP63 is a prognostic gene in breast cancer patients [ 26 ], lung squamous cell carcinoma [ 27 ], pancreatic cancer [ 28 ], skin cutaneous melanoma [ 29 ], anaplastic lymphoma kinase-negative anaplastic large cell lymphoma [ 30 ], etc. STEAP3 is a metal reductase, encoding a transmembrane protein that functions as an iron transporter and coordinates the regulation of iron homeostasis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%